Genome stability of the vaccine strain VAC∆6 - R. A. Maksyutov; S. N. Yakubitskiy; I. V. Kolosova; T. V. Tregubchak; A. N. Shvalov; E. V. Gavrilova; S. N. Shchelkunov (Вавиловский журнал генетики и селекции, 2022)
Due to cessation of mass smallpox vaccination in 1980, the collective immunity of humans against orthopoxvirus infections has virtually been lost. Therefore, the risk of spreading zoonotic human orthopoxvirus infections caused by monkeypox and cowpox viruses has increased in the world. First-generation smallpox vaccines based on Vaccinia virus (VAC) are reactogenic and therefore not suitable for mass vaccination under current conditions. This necessitates the development of modern safe live vaccines based on VAC using genetic engineering. We created the VACΔ6 strain by transient dominant selection. In the VACΔ6 genome, five virulence genes were intentionally deleted, and one gene was inactivated by inserting a synthetic DNA fragment. The virus was passaged 71 times in CV-1 cells to obtain the VACΔ6 strain from the VAC LIVP clonal variant. Such a long passage history might have led to additional off-target mutations in VACΔ6 compared to the original LIVP variant. To prevent this, we performed a genome-wide sequencing of VAC LIVP, VACΔ6, and five intermediate viral strains to assess possible off-target mutations. A comparative analysis of complete viral genomes showed that, in addition to target mutations, only two nucleotide substitutions occurred spontaneously when obtaining VACΔ4 from the VACΔ3 strain; the mutations persisting in the VACΔ5 and VACΔ6 genomes. Both nucleotide substitutions are located in intergenic regions (positions 1431 and 189738 relative to LIVP), which indicates an extremely rare occurrence of off-target mutations when using transient dominant selection to obtain recombinant VAC variants with multiple insertions/deletions. To assess the genome stability of the resulting attenuated vaccine strain, 15 consecutive cycles of cultivation of the industrial VACΔ6 strain were performed in 4647 cells certified for vaccine production in accordance with the “Guidelines for Clinical Trials of Medicinal Products”. PCR and sequencing analysis of six DNA fragments corresponding to the regions of disrupted genes in VACΔ6 showed that all viral DNA sequences remained unchanged after 15 passages in 4647 cells.